PENGARUH AKUNTABILITAS, TRANSPARANSI, DAN PARTISIPASI MASYARAKAT TERHADAP PENGELOLAAN DANA DESA (Studi Kasus Pada 10 Pemerintah Desa di Kecamatan Tahunan Kabupaten Jepara) - Prihasantyo Siswo Nugroho; Panca Wahyuningsih; Siti Alliyah (Jurnal Akuntansi dan Pajak, 2022)
The aim of this study to determine and analyze to determine and analyze the effect of accountability, transparency, and community participation on the management of village funds. The population used in this study were 10 village governments in Tahunan District, Jepara Regency. The research sample was taken using a purposive sampling method with 100 respondents consisting of community leaders in the village government in Tahunan District, Jepara Regency. The research data collection technique was carried out by giving questionnaires directly to 100 respondents who had been determined. The questionnaires were tested for validity and reliability before collecting research data. The data quality test used the classical assumption test which included normality test, multicollinearity test, and heteroscedasticity test. Analysis of the data used to test the hypothesis is multiple linear regression analysis, statistical test F (Goodness of Fit), partial t test, and test the coefficient of determination (Adjusted R Square). The results of this study indicate that accountability, transparency, and community participation have a positive and significant effect on the management of village funds. Keywords: Accountability, Transparency, Community Participation, Village Fund Management